Deep catalytic desulphurization of heavy gas oil at mild operating conditions using self-functionalized nanoparticles as a novel catalyst. (1st December 2017) - El Sayed, Hussien A.; El Naggar, Ahmed M.A.; Heakal, Bassem H.; Ahmed, Nour E.; Said, Sameh; Abdel-Rahman, Adel A.H.
Highlights: Synthesis of novel cobalt nanoparticles by the electroless platting technique. Characterization of the prepared material using different tools. Investigating its efficiency in sulphur removal at different conditions. New advances are detected at the end of study. Abstract: The desulphurization of diesel fuel fractions in order to obtain environmental friendly fuel has been extensively demanded worldwide. This in turn can positively minimize the harmful emissions; hence low potentiality for serious problems to take place. The utilization of effective chemical materials in order to attain this goal is always requested. In line with that trend, this research work is dedicated to the production of a low sulphur diesel fuel. The current study summarizes new advances in the desulphurization process based on some different perspectives. Firstly, nanoparticles of a novel cobalt structure are introduced as a selective material for the desulphurization, unlike the commonly known ones which are basically metals oxides. The production of a low sulphur diesel fuel accompanied with extremely low operating conditions is another advance, as revealed in this work. Approximately, 85% of the sulphur content in the starting feedstock was removed at the final diesel fuel at non-severe conditions.